(untitled) (Journal of Transport System Engineering, 2026)
study numerically investigates the effect of leading-edge sweep angle on the aerodynamic performance of a generic Stability and Control Configuration (SACCON) unmanned combat aerial vehicle (UCAV). Three configurations with leading-edge sweep angles of 45°, 53°, and 60° were modelled and simulated using computational fluid dynamics (CFD) in ANSYS Fluent. A virtual wind-tunnel domain with a freestream velocity of 50 m/s was used, and the simulations were performed using the Spalart–Allmaras turbulence model at angles of attack of 5°, 10°, 15°, and 20°. The lift coefficient, drag coefficient, lift-to-drag ratio, and surface pressure distribution were evaluated for each configuration. The results show that the leading-edge sweep angle influences both lift and drag characteristics, particularly at higher angles of attack. The 53° reference configuration produced higher lift and drag at 20°, while the 45° configuration showed better lift-to-drag performance at higher angles of attack. The findings indicate that leading-edge sweep modification affects the aerodynamic efficiency of SACCON-type UCAV configurations and should be considered carefully in early-stage aerodynamic design.